MICRO SIMULATION OF PELICAN CROSSING AT THE ROAD SECTION OF COLOMBO STREET, YOGYAKARTA USING THE AIMSUN SOFTWARE - , ANGGRAENI HAPSARI, Prof. Dr. Ir. Siti Malkhamah, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Yogyakarta, one of the the largest cities in Indonesia and wellknown as the students and tourism city, has the problem related to pedestrians. The mixed traffic makes pedestrian as the vulnerable road user not to obtain the priority when crossing the street. Some difficulties in terms of delay, safety and convenience are experienced by most pedestrians. Inappropriate implementation of crossing facility and disobedience of pedestrians while crossing the street lead to the conflicts between pedestrians and vehicular traffic as well. Taking the road section of Colombo Street as the case study, this research proposes pelican crossing with independent and coordination time signal operation. Later on, the performances resulted of the implementation of pelican crossing are compared to obtain the best alternative. In addition, this research assesses the relationship between vehicle speed and the pedestrian safety. Colombo Street is located between Sagan signalised intersectiona and Gejayan signalised T-junction. Using Aimsun software, the existing traffic signal, geometric design, traffic flow and turning proportion are taken into account to build the initial model. Afterwards, the calibration of queue length and validation of vehicle speed are carried out to obtain the basic model which represents the existing condition of the system. The basic model is developed by implementing signal time crossing facility, i.e. pelican crossing either with independent operation or coordination operation. Comparing the basic model and the alternatives in terms of performances of junctions, road section and pedestrians in the pelican, this research results in setting the double cycling of pelican at 100 seconds for the independent operation and setting the common cycle time at 120 seconds for the coordination operation as the best alternatives. In addition, the implementation of the pelican crossing brings about the reduction of the vehicle speed in the road section so that the safety of the pedestrian increases. Yet, the signal coordination leads to the higher vehicle speed in the road section than without the coordination signal since the green wave allows the vehicles to travel continuously